Foreign Direct Investment in East Asia and Latin America: Is there a People's Republic of China Effect? - Busakorn Chantasasawat; K. C. Fung; Hitomi Iizaka; Alan Siu (Asian Development Bank Institute (ADBI), 2005)
In recent years, the People's Republic of China (PRC) has emerged as the world's largest recipient of foreign direct investment (FDI). Many analysts and government officials in the developing world have expressed concern that they are losing competitiveness to the PRC. Is the PRC diverting FDI from other developing countries? Theoretically, a growing PRC could add to other countries' FDI by creating more opportunities for production networking and raising the need for raw materials and resources. At the same time, the extremely low labor costs in the PRC might lure multinational enterprises (MNEs) away from other developing countries when they considered alternative locations for low-cost export platforms. In this paper, we explore this important research and policy issue empirically. We focus on East and Southeast Asia as well as Latin America. For Asia, we use data for eight economies (Hong Kong, China, Taipei,China, Republic of Korea, Singapore, Malaysia, Philippines, Indonesia and Thailand) for 1985-2002, while for Latin America, we use data for sixteen economies (Argentina, Bolivia, Brazil, Chile, Columbia, Costa Rica, Ecuador, El Salvador, Guatemala, Mexico, Nicaragua, Panama, Paraguay, Peru, Uruguay and Venezuela) for 1990–2002. We control for the standard determinants of inward direct investment. We then add the PRC's inward FDI as an indicator of the “PRC Effect.” An estimation of the coefficient associated with the PRC Effect proxy gives us indications about its existence. We obtain three results: (1) the level of the PRC's foreign direct investment is positively related to the levels of inward direct investments of economies in East and Southeast Asia, while it is mostly insignificant for Latin American economies; (2) the level of the PRC's FDI is negatively related to the direct investment into these economies as shares of total foreign direct investments in the developing countries; (3) the PRC Effect is generally not the most important determinant of inward direct investment for these economies. Market size and policy variables such as openness and corporate tax rates tend to be more important.
hdl:11540/4172
Keywords: 330; Auslandsinvestition; Internationaler Wettbewerb; Ostasien; Lateinamerika; China